2019
DOI: 10.1038/s41598-019-42677-x
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees increase their foraging performance and frequency of pollen trips through experience

Abstract: Honey bee foragers must supply their colony with a balance of pollen and nectar to sustain optimal colony development. Inter-individual behavioural variability among foragers is observed in terms of activity levels and nectar vs . pollen collection, however the causes of such variation are still open questions. Here we explored the relationship between foraging activity and foraging performance in honey bees ( Apis mellifera ) by using an automated behaviour monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 63 publications
(64 reference statements)
2
44
0
1
Order By: Relevance
“…Metabolic rate increased with total mass for bees in both loading conditions (heavy, R 2 = 0.7277; light, R 2 = 0.7327), but the slope of this relationship was significantly lower for bees carrying heavy loads (interaction of mass and treatment  2 1 = 7.17, P = 0.0074). (B) A proxy for translational force production (wing area × average wing velocity2 ; SU w increased with total mass of the bee plus load, as expected (heavy, R 2 = 0.8496; light, R 2 = 0.7921). The slope of this relationship was not significantly different for bees carrying light versus heavy loads.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Metabolic rate increased with total mass for bees in both loading conditions (heavy, R 2 = 0.7277; light, R 2 = 0.7327), but the slope of this relationship was significantly lower for bees carrying heavy loads (interaction of mass and treatment  2 1 = 7.17, P = 0.0074). (B) A proxy for translational force production (wing area × average wing velocity2 ; SU w increased with total mass of the bee plus load, as expected (heavy, R 2 = 0.8496; light, R 2 = 0.7921). The slope of this relationship was not significantly different for bees carrying light versus heavy loads.…”
supporting
confidence: 64%
“…Foraging eusocial bees can spend many hours per day collecting and carrying loads of nectar and pollen back to their nest to meet the energetic and nutritional requirements of the queen, other workers, and developing brood (1,2). The quantity of resources collected by foragers is critical to hive growth and the production of new reproductive queens (3) and thus to the fitness of the hive as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the number of very active foragers in a hive is an important factor. In a very recent study, researchers showed that only 19% of the total forager performed 50% of the colony's total foraging trip (Klein et al, 2019). Thus, these factors could be plausible reasons for different foraging pollen amounts of the honey bee colonies.…”
Section: Discussionmentioning
confidence: 99%
“…One main critical aspect of life-history in honey bees are the ontogenetic shifts at the adult stage (Visscher & Dukas, 1997; Becerra-Guzman, Guzman-Novoa, Correa-Benitez, & Zozaya-Rubio, 2005; Rueppell, Bachelier, Fondrk, & Page, 2007; Perry, Søvik, Myerscough, & Barron, 2015; Klein et al, 2019). The “Age at Onset of Foraging” (AOF) –defined as the age at the onset of foraging activity per se when adult bees have completed the learning phase occurring during orientation flights (Capaldi, & Dyer, 1999; Capaldi et al, 2000; Degen et al, 2016)– is arguably a critical fitness trait of honey bees at both individual and colony levels (Perry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hence the duration and the number of trips, as proxies of time-activity budgets, should differ between learning and foraging, and AOF was thus commonly defined using arbitrary thresholds. For instance, ontogenetic shift was defined as the first day that a bee performs 5 trips or performs a trip longer than 30 minutes (Calderone & Page, 1988; Dukas, 2008, Tenczar, Lutz, Rao, Goldenfeld, & Robinson, 2014; He, Tian, Wu, & Zeng, 2015; Perry et al, 2015; Klein et al, 2019). However, the use of arbitrary thresholds may fail to capture the true timing of ontogenetic shifts, given the high inter-individual variation in honey bee life-history traits (Huang & Robinson, 1996; Amdam et al, 2009; Perry et al, 2015), and may differ with the genetic composition of the colony (Calderone & Page, 1988; Becerra-Guzman et al, 2005), climatic environmental factors (Henry et al, 2014; He et al, 2015), landscape structure and composition (Henry et al, 2014), and pesticide exposure (Decourtye et al, 2011; Henry et al, 2012; Prado et al, 2019).…”
Section: Introductionmentioning
confidence: 99%